Jeu, matérialité et politique chez Walter Benjamin - Federico Tarragoni (Tracés, 2015)
For anyone who wants to take up the challenge of thinking about the relationship between play and materiality, the work of Walter Benjamin (1892-1940) proves particularly inspiring. Benjamin outlines a phenomenology of play in his work on childhood – which is scattered among general philosophical remarks, the social and cultural history of toys, and educational discussions of the emancipation of the child. Play should be understood as the basis of several activities : the confrontation and appropriation of materials, the training experience and genesis of a dialectical imagination. However, the analysis of the materiality of games is not limited to childhood; in his work on the 19th century, Benjamin’s gambler becomes one of the “utopian scouts” of modernity. An analytical constant remains, from games to gambling, from children to players: the game opens a space for the practice of freedom, through an assumed relation between humans and objects, the individual and time. Therefore, the game is not political in its content, but in the social relationships it establishes and revokes: this is the main Benjaminian contribution to a sociology of the game understood as a sociology of culture.